EURASIA AMIDST THE SPIRIT OF SHANGHAI AND A COMMUNITY OF SHARED FUTURE - Concepción, Sunamis Fabelo (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article is based on the analysis of the integrationist trends that have evolved in Central Asia between 1991 and 2015. It deals with how the historical reality of the Central Asian republics conditioned them to search for centers of reference to guide the construction of their political and economic systems. This situation caused these countries, since their independence, to begin to interact with important international relations players, with whom they built a series of interdependent relations that were tracing two integrationist conceptions that became trends: Western and Eurasian. The latter one is the one that has most advanced in the period studied, promoted by Russia and China with the implementation of important mechanisms of association, cooperation and consensus, among which the Shanghai Cooperation Organization, the Eurasian Economic Union and the New Silk Road project. In this sense, the Chinese megaproject One Belt One Road is supported by a series of conceptual bases as a result of the progress and evolution of the Eurasian trend understood in its broader meaning.